Defining regional recycling indicators for metals: An extension of global recycling indicators to regional systems with open boundaries - Luis Alberto Tercero Espinoza; Marcel Soulier (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2017)
Recycling indicators are useful for characterizing anthropogenic metal cycles. While there are suitable and generally accepted recycling indicators at the global level, they are not necessarily useful for regional cycles (where the region of interest can be a part of country, an entire country or a group of countries), which are open and interact with other regions such that cross-border flows need to be considered. Herein, we examine the applicability of available (global) recycling indicators to the regional level and, where appropriate, propose modified versions that are both conceptually compatible with the corresponding global indicators and readily accessible through data collected and estimates generated in regional material flow analysis work.
urn:nbn:de:0011-n-4357737
Keywords: 330; recycling rates; foreign trade